Adaptação e evidências de validade do Inventário de Modos Esquemáticos (Schema Mode Inventory) (SMI) para população brasileira - Damasceno, Elisa Steinhorst (2020)
Scheme Therapy (ST) was developed to treat patients with chronic symptoms, characterological disorders or Personality Disorders (PDs). Having a Cognitive-Behavioral basis, ST integrates elements of attachment theory, object relations, psychodynamic approaches, cognitive-analytical therapy, personal schemes, focused on emotion and GestaltTherapy. Three fundamental pillars underpin the approach: the concept of Early Maladaptive Schemas (EMSs, or schema); maladaptive coping strategies (also called styles or responses); and the concept of Schema Modes (also called SMs or modes), later developed. Latent structures related to personality traits, EMSs are composed of cognitions, emotions and bodily sensations. They are developed in childhood and adolescence, as consequences of not satisfying basic emotional needs, from the interaction between environmental conditions and innate predispositions. Schemas are developed throughout life, being activated from trigger situations that elicit coping responses based on overcompensation, avoidance or resignation. When activated, both individually and in groups, schemas and coping strategies interfere in the individual's functioning, determining different ways of feeling, thinking and acting. Representing the emotional state in which the individual is at a given moment, these different configurations of feelings, thoughts and behavioral tendencies are called Schema Modes (SMs). The approach based on SMs was developed to assist in the understanding and treatment of patients with severe Personality Disorders, allowing the different sets of internalizing and externalizing symptoms that make up these disorders to be identified in terms of modes. In order to facilitate the identification of these structures, both in the clinical and research context, the Schema Mode Inventory (SMI) was developed. It is a self-report instrument that measures the activation frequency of 14 modes, with 124 items scored on a six-point Likert scale. The present dissertation has as general objective to present the processes of adaptation and study of the evidence of validity of the SMI for use in Brazil. Initially, a theoretical section is presented with justification on the topic. The origin of Schema Therapy and the term Early Maladaptive Schemas are discussed in detail, as well as the concept of Schema Modes and the context in which it was developed. The reasons why the ST approach based on Modes has been gaining space and relevance are explored, justifying the importance of adapting and validating the instrument to the Brazilian context, also citing studies that carried out these processes in other countries. After the theoretical foundation, an empirical section is presented with the study entitled “Adaptação e Evidências de Validade do Inventário de Modos Esquemáticos (Schema Mode Inventory) (SMI) para a população brasileira” (Adaptation and evidence of validity of the inventory of schematic models for the Brazilian population). Firstly, the study describe the process of adapting the SMI for use in Brazil, following the guidelines of the institution that then held the copyright for the instrument, the Schema Therapy Institute (STI), which granted formal authorization to carry out this process. Then, the evidence of validity of the Inventory is presented, and the processes carried out for this purpose are described. The sample was selected for convenience, and 1,027 individuals from the general population participated in the study. In addition to the SMI, the Young-Rygh Avoidance Inventory (YRAI), the Young's Compensation Inventory (YCI), the Young's Scheme Questionnaire - short version (YSQS3) and the Symptom Checklist (SCL-90) were applied. The collection was performed through an online platform and paper and pen. Confirmatory Factor Analysis (CFA) was performed to investigate the instrument's factorial structure, in the R environment, utilizing the lavaan package. The convergent validity was verified from the analysis of the correlations between Schema Modes, Early Maladaptive Schemas, Avoidance and Overcompensation Coping Strategies and clinical psychological symptoms. Fitting indexes to the factorial model were considered adequate, with relative χ² of 2,4, SMRSR = 0.065, RMSEA = 0.042, CFI = 0.9 and TLI = 0.9. The subscales showed adequate internal consistency, varying from α = 0.70 and Ω = 0.71 to α =0.90, Ω = 0.91. The standardized factor loadings were all statistically different from zero and, for the most part, over 0.3, which was the value established as a criterion. The analysis of bivariate correlations showed patterns of convergence, mostly corresponding to those a priori hypothesized, and the most relevant results from the theoretical point of view were discussed. The present study found good evidence that the Brazilian version of the SMI has satisfactory psychometric properties, being considered an adequate instrument to be used in the Brazilian context, both in research and in clinical practice.